Evaluation of the safety and efficacy of codeine phosphate and chlorpheniramine maleate in a fixed dose composition for the management of dry cough in adults: an open label phase IV clinical trial - Kumar, Ashok; Batra, Jyoti (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Dry cough is one of the most common symptoms for which patients seek medical attention. It not only causes discomfort in patients, but also hampers their daily work and routine. Since there is no specific underlying cause for dry cough, a definitive treatment is still not available. Several cough suppressants have been used for the treatment of dry cough including codeine which reduces discomfort. However, some reports suggest that use of codeine at high doses leads to sedation and drowsiness. To evaluate the safety and efficacy of codeine, a clinical trial for fixed dose composition of codeine phosphate and chlorpheniramine maleate was conducted. Methods: The trial was conducted on 219 adults with prior symptoms of dry cough. Safety was evaluated on the basis of the change in patient’s vital parameters, any adverse event or severe adverse event that occurred during the course of study. Efficacy was assessed on the basis of cough severity scores, number of night awakenings due to cough, and overall decline in cough. Results: According to the investigator's evaluation the product was safe to use as no significant changes in the patient’s vital parameters were observed during the course of study. Also, no severe adverse events were reported. Administration of the investigation product significantly decreased cough severity and frequency at the 7th day of the study. Conclusions: This study suggests, FDC of codeine phosphate 10 mg and chlorpheniramine maleate 4 mg per 5 ml oral syrup is safe and efficacious for the treatment of dry cough.